PDCT-13. ENTRECTINIB IN CHILDREN AND ADOLESCENTS WITH RECURRENT OR REFRACTORY SOLID TUMORS INCLUDING PRIMARY CNS TUMORS. (11th November 2019) - Robinson, Giles; Desai, Ami; Gauvain, Karen; Basu, Ellen; Dorris, Kathleen; Maese, Luke; Sabnis, Amit; Foster, Jennifer; Shusterman, Suzanne; Yoon, Janet; Weiss, Brian; Abdelbaki, Mohamed; et al.
Abstract: The phase 1/2 STARTRK-NG trial is evaluating entrectinib, a CNS-penetrant oral inhibitor of TRK, ROS1 and ALK tyrosine kinases, in children with solid tumors, including primary CNS tumors. Eligible patients are ≤22y with recurrent/refractory solid tumors. The recommended dose was determined in all-comers, and then expansion cohorts of CNS and solid tumors with NTRK1/2/3, ROS1 or ALK gene fusions, and neuroblastomas (NBL) regardless of mutation spectrum, were enrolled. Investigator-assessed response was classified as complete (CR) or partial response (PR), stable (SD) or progressive disease using RANO (CNS), RECIST (solid tumors), or Curie score (NBL). By the clinical data cut-off, 01 April 2019, 32 patients were enrolled. As of 31 Oct 2018 (enrollment data cut-off), 29 patients were enrolled and included in the evaluable population. Median age was 7y (range 4.9m to 20y). Entrectinib was well tolerated; phase 1 dose-limiting toxicities were: elevated creatinine, dysgeusia, fatigue, and pulmonary edema. The recommended dose was 550mg/m 2 daily; all responses occurred at doses ≥400mg/m 2 . In 6 patients with high-grade CNS tumors, all gene-fusion-positive, ORR was 100% (Investigator-assessed responses): 2 CR ( ETV6-NTRK3, EML1-NTRK2 ); 4 PR ( TPR-NTRK1, KANK1-NTRK2, EEF1G-ROS1, GOPC-ROS1 ). In extracranial solid tumors 6/8 had a fusion; of these, 2 achieved a confirmed CR ( DCTN1-ALK, ETV6-NTRK3 ), and 4 achieved PR ( ETV6-NTRK3, EML4-NTRK3, TFG1-ROS1, KIF5B-ALK ). Central imaging review is being performed and will be provided. Duration of therapy ranged from 0.2 to 22.2 months for all 32 patients. In responding patients, time to response ranged from 1 to 8.3 months. In children with refractory CNS tumors harboring NTRK1/2/3 or ROS1 fusions, entrectinib produced striking, rapid, and durable responses. No responses were seen in tumors lacking target gene fusions. These results support the continued evaluation of entrectinib in solid tumors with target gene fusions, especially high-grade CNS neoplasms.